Structural and functional characterization of a novel molluskan ortholog of TRAF and TNF receptor - associated protein from disk abalone (Haliotis discus discus) - Lee, Y.; Elvitigala, D. A. S.; Whang, I.; Lee, S.; Kim, H.; De Zoysa, M; Oh, C.; Kang, D.H.; Lee, J. (Elsevier, 2014)
Immune signaling cascades have an indispensable role in the host defense of almost all the organisms. Tumor necrosis factor (TNF) signaling is considered as a prominent signaling pathway in vertebrate as well as invertebrate species. Within the signaling cascade, TNF receptor-associated factor (TRAF) and TNF receptor-associated protein (TTRAP) has been shown to have a crucial role in the modulation of immune signaling in animals. Here, we attempted to characterize a novel molluskan ortholog of TTRAP (AbTTRAP) from disk abalone (Haliotis discus discus) and analyzed its expression levels under pathogenic stress. The complete coding sequence of AbTTRAP consisted of 1071 nucleotides, coding for a 357 amino acid peptide, with a predicted molecular mass of 40 kDa. According to our in-silico analysis, AbTTRAP resembled the typical TTRAP domain architecture, including a 50 -tyrosyl DNA phosphodiesterase domain. Moreover, phylogenetic analysis revealed its common ancestral invertebrate origin, where AbTTRAP was clustered with molluskan counterparts. Quantitative real time PCR showed universally distributed expression of AbTTRAP in selected tissues of abalone, from which more prominent expression was detected in hemocytes. Upon stimulation with two pathogen-derived mitogens, lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (poly I:C), transcript levels of AbTTRAP in hemocytes and gill tissues were differentially modulated with time. In addition, the recombinant protein of AbTTRAP exhibited prominent endonuclease activity against abalone genomic DNA, which was enhanced by the presence of Mg2þ in the medium. Collectively, these results reinforce the existence of the TNF signaling cascade in mollusks like disk abalone, further implicating the putative regulatory behavior of TTRAP in invertebrate host pathology.
Keywords: TTRAP; Disk abalone; Gene ontology; Endonuclease activity; Transcriptional analysis